HUBUNGAN KELENTUKAN PERGELANGAN TANGAN DENGAN AKURASI PUKULAN BACKHAND DALAM PERMAINAN TENIS MEJA PADA ATLET PUTERA CLUB TENIS MEJA PERSATUAN TENIS MEJA MANDIRI - Adri Alhamdi; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this study was to find out how much the relationship of wrist bandage with the accuracy of backhand punch in a table tennis game at the club of Unity Table Tennis Mandiri. The type of research is correlational research. Samples taken as many as 19 athletes daughter of Unity Table Tennis Mandiri Pandau. Prior to the purpose of correlation test, normality test with Lilliefors test, normality test to the research variable showed that the test result data of wrist flexibility ability after calculation resulted Lhitung at 0.211, backhand Lhitung 0121, and Ltabel 0,234. This means Lhitung is smaller than Ltabel. It can be concluded that the distribution of data is normally distributed. Next Based on t test analysis yield rhitung of -0.08. From the results of the above analysis it can be concluded that there is a relation of wrist formation (X1) with the ability of backhand punch (Y) in table tennis game on athlete of club tennis player table tennis of Mandiri Table Tennis. Keywords: Handle establishment Accuracy Backhand